1997
DOI: 10.1210/en.138.6.2227
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by Thyroid-Stimulating Hormone of Sodium/Iodide Symporter Gene Expression and Protein Levels in FRTL-5 Cells

Abstract: To investigate the mechanism of I- transport stimulation by TSH, we studied the effects of TSH on Na+/I- symporter (NIS) messenger RNA (mRNA) and protein levels in FRTL-5 cells and correlated these with I- transport activity. When 1 mU/ml TSH was added to quiescent FRTL-5 cells, a 12-h latency was observed before the onset of increased I- transport activity, which reached a maximum [approximately 27 times basal (5H medium) levels] at 72 h. In contrast, Northern blot analysis, using rat NIS complementary DNA as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
128
0
6

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(149 citation statements)
references
References 0 publications
15
128
0
6
Order By: Relevance
“…It has been reported that the iodide uptake in thyroid cells is stimulated by TSH via the cAMP͞adenylate cyclase pathway (4,7,8,37). Treatment of MCF-7 cells with 0.1-100 M forskolin, an agonist of adenylate cyclase, however, did not increase the iodide uptake (data not shown).…”
Section: Iodide Efflux Is Relatively Low In Mcf-7 Cells Compared Withmentioning
confidence: 81%
See 2 more Smart Citations
“…It has been reported that the iodide uptake in thyroid cells is stimulated by TSH via the cAMP͞adenylate cyclase pathway (4,7,8,37). Treatment of MCF-7 cells with 0.1-100 M forskolin, an agonist of adenylate cyclase, however, did not increase the iodide uptake (data not shown).…”
Section: Iodide Efflux Is Relatively Low In Mcf-7 Cells Compared Withmentioning
confidence: 81%
“…The up-regulation of NIS by TSH in thyroid cells has been well characterized (4,7,37) and contrasts with tRA stimulation in MCF-7 cells. NIS mRNA levels are rapidly increased in TSH-stimulated FRTL-5 rat thyroid cells; however, there is a 12-h latency before the onset of increased iodide uptake and maximum uptake is observed at 72 h (7,37). In contrast, in MCF-7 cells, tRA increased NIS mRNA, NIS protein, and iodide uptake levels by 6 h, reaching a maximum at 12, 24, and 48 h, respectively, and no latency period of iodide uptake was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the impairment of hNIS gene expression occurring in hypofunctioning thyroid tumors could simply result from a switching off of the pathway controlling the expression of hNIS gene. In vitro studies on thyroid cell models and in vivo studies in rodents indicate that the main regulator of NIS gene expression is TSH and that the hormone primarily acts at the level of transcription, [23][24][25][26][27] but also exerts posttranscriptional regulatory actions. 21 Because patients with a cold nodule, be it an adenoma or a carcinoma, are generally euthyroid with a plasma TSH concentration within the normal range, and as TSH receptor expression is maintained in these tumors, 28 it is reasonable to think that the impairment of hNIS expression occurring in hypofunctioning thyroid tumors could result from alterations of regulatory elements along the TSH-activated pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Cells and culture conditions FRTL-5 cells were cultured in Coon's modified Ham's F12 medium with 5% calf serum and a six-hormone mixture (6H) composed of insulin (10 ag/ml), cortisone (10 nM), human transferrin (5 ig/ml), glycyl-L-histidyl-L-lysine (10 ng/ml), somatostatin (10 ng/ml ) and TSH (1 mU/ml), as described previously [9,10]. Cells were maintained at 37°C in an atmosphere saturated with water and containing 95% air-5% C02.…”
Section: Methodsmentioning
confidence: 99%